PENENTUAN Cu, Pb, Cd, dan Zn DALAM AIR SECARA STRIPPING POTENTIOMETRI DENGAN ELEKTRODA KONVENSIONAL DAN KOMBINASI - E. Sahara (Jurnal Kimia (Journal of Chemistry), 2008)
This paper discusses the development of stripping potentiometric methods for reliable determination of Cu,Pb, Cd, and Zn in natural water. The electrode systems used were the conventional and combined ones. Theformation of intermetallic compound between Cu and Zn was overcame with the addition of gallium ions. Themethod involved two stripping cycles during which copper was initially determined on its own, followed bysimultaneous determination of Pb, Cd and Zn after addition of 150 mg/L gallium ions. The optimum conditions forreliable determination of the metals with the use of the conventional electrode were 0.01 M HCl, 10 mg/L Hg (II), adeposition potential of -1200 mV and a deposition time of 30 seconds, while those with the use of the combinedelectrode included 0.01 M HCl, 10 mg/L Hg (II), a deposition potential of -700 mV for Cu and -1300 mV for theother three metals and a deposition time of 10 seconds. It was also found that the use of the combined electrode gavelower detection limit and wider linear concentration range for the four metals.